2015
DOI: 10.3402/jev.v4.28621
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from apoptotic RAW 264.7 macrophage cells carry tumour necrosis factor‐α functionally active on cardiomyocytes from adult mice

Abstract: After ischaemic injury and in patients with atherosclerosis, the pool of inflammatory macrophages is enlarged in the heart and in atherosclerotic plaques. Monocyte/macrophage-derived microparticles (MPs) are part of the pathological process of unstable atherosclerotic plaques. The present study focused on effects of MPs, produced by apoptotic murine RAW 264.7 macrophage cell line, in adult murine cardiomyocytes. Flow cytometry and western blot analysis showed that these MPs contained the soluble form of tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Microparticles are produced by macrophage cells in response to various stimuli such as lipopolysaccharide (LPS), poly (I:C), actinomycin D [ 14 , 15 ]. LPS is a toll-like receptor (TLR)-4 ligand, and poly (I:C) is a TLR3 ligand that can stimulate MØ-MP via TLR.…”
Section: Introductionmentioning
confidence: 99%
“…Microparticles are produced by macrophage cells in response to various stimuli such as lipopolysaccharide (LPS), poly (I:C), actinomycin D [ 14 , 15 ]. LPS is a toll-like receptor (TLR)-4 ligand, and poly (I:C) is a TLR3 ligand that can stimulate MØ-MP via TLR.…”
Section: Introductionmentioning
confidence: 99%
“…After application of MPs, there was increased expression of apoptosis regulator bcl-2-like protein 4 (Bax), caspase-8, caspase-3, and cytochrome C in cardiomyocytes. These results provide evidence that MPs released from activated macrophages possessing TNF- α could contribute to the promotion of vascular inflammatory signals leading to atherosclerosis and myocardial infraction [ 43 ].…”
Section: Role Of Emps On Pathogenesis Of Atherosclerosismentioning
confidence: 96%
“…Macrophages release EVs containing mRNAs that help to identify the phenotype of the parent cells 59 . Using mass spectrometry, the contents of EVs derived from macrophages that were exposed to LPS were identified and included groups of functional proteins, such as plasma membrane-associated proteins, chaperones, metabolic enzymes, cytokines, alarmins, and damage-associated molecular patterns 60 - 62 . It was also shown that macrophage-EVs were enriched in the active accessible pool of cholesterol, which increased the efficiency of cholesterol transfer to high-density lipoprotein, thus lowering the cholesterol level 63 .…”
Section: Characteristics and Functions Of Evs From Cells Associated Wmentioning
confidence: 99%